The Role of Nurse Engagement and Change Management in Improving Patient Outcomes: Evidence from Riyadh Health Clusters - Almotairi, Salah; Ali, Dhakir Abbas; Said, Faridah Mohd; Aladhyani, Saleh Ishq (Genius Journal, 2025)
Introduction: Riyadh’s healthcare reforms under Vision 2030 emphasize patient outcomes as key quality indicators. This study examines the underexplored interplay between nurse engagement and change management in shaping healthcare performance within Riyadh Health Clusters. Objective: This study aimed to examine the impact of nurse engagement and change management on patient outcomes within Riyadh Health Clusters. Methods: A quantitative research design was employed, involving 384 healthcare professionals from three clusters. Nurse engagement and change management were analyzed as independent variables, while patient outcomes served as the dependent variable. Data were processed using linear regression analysis in SPSS with a 5% significance threshold. Results: The findings demonstrated that nurse engagement strongly predicted patient outcomes (R = 0.72; R² = 0.71; β = 0.64; p < 0.05), showing that higher engagement levels significantly improved care quality. Change management practices also had a positive but more moderate effect on patient outcomes (R = 0.47; R² = 0.22; β = 0.45; p < 0.05). Conclusion: This study demonstrates that nurse engagement is a strong predictor of patient outcomes, while change management also contributes positively, though to a lesser extent. The findings emphasize that investing in strategies to enhance nurse engagement, such as professional development, participatory decision-making, and supportive leadership, is critical to improving the quality of care. At the same time, structured change management remains essential to sustain organizational adaptation and innovation in healthcare delivery. Together, these insights highlight the importance of integrating workforce-centered initiatives with system-level reforms to strengthen patient-centered outcomes within Riyadh Health Clusters and beyond.